Differential T-Cell Reactivity to Endemic Coronaviruses and SARS-CoV-2 in Community and Health Care Workers. (2nd April 2021) - da Silva Antunes, Ricardo; Pallikkuth, Suresh; Williams, Erin; Dawen Yu, Esther; Mateus, Jose; Quiambao, Lorenzo; Wang, Eric; Rawlings, Stephen A; Stadlbauer, Daniel; Jiang, Kaijun; Amanat, Fatima; Arnold, David; et al.
Abstract: Herein we measured CD4 + T-cell responses against common cold coronaviruses (CCC) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in high-risk health care workers (HCW) and community controls. We observed higher levels of CCC-reactive T cells in SARS-CoV-2–seronegative HCW compared to community donors, consistent with potential higher occupational exposure of HCW to CCC. We further show that SARS-CoV-2 T-cell reactivity of seronegative HCW was higher than community controls and correlation between CCC and SARS-CoV-2 responses is consistent with cross-reactivity and not associated with recent in vivo activation. Surprisingly, CCC T-cell reactivity was decreased in SARS-CoV-2–infected HCW, suggesting that exposure to SARS-CoV-2 might interfere with CCC responses, either directly or indirectly. This result was unexpected, but consistently detected in independent cohorts derived from Miami and San Diego. CD4+ T-cell responses against common cold coronaviruses (CCC) are elevated in SARS-CoV-2 seronegative high-risk health care workers (HCW) compared to COVID-19 convalescent HCW, suggesting that exposure to SARS-CoV-2 might interfere with CCC responses and/or cross-reactivity associated with a protective effect. Abstract : CD4 + T-cell responses against common cold coronaviruses (CCC) are elevated in SARS-CoV-2 seronegative high-risk health care workers (HCW) compared to COVID-19 convalescent HCW, suggesting that exposure to SARS-CoV-2 might interfere with CCC responses and/or cross-reactivity a protective effect.